Principal's academic supervision management in fostering teacher professional competence - Cut Nadia Sofia; Yusrizal Yusrizal; Khairuddin Khairuddin (AL-ISHLAH: Jurnal Pendidikan, 2022)
The success and achievement of teaching objectives is influenced by the role of the principal in improving teacher competence, and the ability of supervisors. The purpose of this study was to determine the academic supervision program, the implementation of academic supervision and evaluation of the supervision applied by the principal in fostering the professional competence of teachers at Al-Azhar Middle School Cairo Banda Aceh. This study uses a descriptive analysis method with a qualitative approach. Data collection techniques through observation and interviews. The subjects in this study were principals and teachers of SMP Al-Azhar Cairo Banda Aceh. The data analysis technique used is descriptive qualitative analysis, while the data processing steps are data reduction, data display, and conclusions and data verification. The results of the study found that: (1) In the preparation of the academic supervision program so far it has been carried out jointly or through deliberation which was attended by the principal, vice principal and also the teacher council, 2) So far, the principal has carried out academic supervision on a scheduled, regular and regular basis. structured based on an invitation to the teacher council with advance notice before the implementation of academic supervision is carried out at the beginning of the new school year. 3) In evaluating the results of academic supervision, it was found that there was preparation of learning (learning tools), curriculum implementation to be achieved according to the specified time, teachers must be creative and active in carrying out their duties, maintain good attitudes and behavior 4) follow-up academic supervision including planning, implementation, and assessment, good coaching has been carried out in accordance with existing procedures, but the principal must maintain innovation and creativity in conducting academic supervision. The conclusion is that school principals often carry out other activities such as guiding, directing, assisting teachers, attending seminars both online and offline, upgrading and also inviting competent resource persons, so that the professional competence of teachers is further increased.